Enhancing Community Engagement for Sustainable Educational Outreach in Urban Environments: An Action Research Study - Rebecca Hardeman; Alexandra Cox (Adult Education Research Conference, 2024)
Cooperative Extension currently faces engagement challenges in urban areas. This roundtable will explore research on boosting outreach and engagement in urban areas for Extension professionals.
Keywords: cooperative extension; action research; complex adaptive systems; urban; organization development